The Relationship Between the Level of Administrative Performance and The Level of Administrative Creativity Among the Administrative Members of The Golden Square Clubs in The Iraqi League - Alhamdane, Aktham; Boukari, Samia; Mhenni, Thouraya; Attia, Ahmed; Turki, Olfa; Gaied Chortane, Sabri; Khalifa, Riadh (Advances in Social Sciences Research Journal, 2024)
This study aims to identify the relationship between the level of administrative performance and the level of administrative creativity among of the administrative members of the Golden Square clubs in the Iraqi league. Additionally, it sought to identify differences in the level of managerial performance and managerial creativity among the administrative members of the Golden Square Clubs in the Iraqi League based on the variables of educational qualification and specialization. To achieve this objective, the study was carried out with a sample of forty-eight (48) administrative members of the Golden Square Clubs. Two study instruments were prepared for data collection. The first instrument was the managerial performance tool consisting of 39 items distributed across four areas (planning, organizing and coordinating, directing and controlling, communication and decision-making). The second instrument was the managerial creativity tool consisting of 38 items distributed across four areas (encouraging creativity, problem-solving and decision-making, adaptability to change, spirit of risk-taking). The results of this study indicated that the managerial performance of the administrative members in the Golden Square Clubs was high, with a response rate of 74.93%. However, managerial creativity among the administrative members in Iraqi sports clubs was average, with a response rate of 71.23%. These results also revealed a statistically significant positive correlation at a significance level of 0.05 between the level of managerial performance and managerial creativity among the administrative members in Iraqi sports clubs. The correlation coefficient was high, reaching a value of 0.84. Furthermore, the study identified statistically significant differences at a significance level of 0.05 in the level of managerial performance among the administrative members in Iraqi sports clubs, attributed to the variables of educational qualification and specialization.